Development of methodological bases for the foresight model of youth entrepreneurship development - Khussainova, Zh.S.; Zhartay, Zh.M. (BUKETOV BUSINESS REVIEW, 2020)
Objective: development of methodological bases for the foresight model of youth entrepreneurship development. Methods: methods of system based, structural and functional analysis. Findings: specification of the specifics of the foresight method in the development of long-term development strategies with perspective extrapolation to modeling the development of youth entrepreneurship. Conclusions: The foresight analysis of youth entrepreneurship does not have an independent character, but is a factor element of technological foresight, cluster foresight, and sociological foresight. This approach is also productive, since it allows you to use additional in-depth analysis materials and contribute to the formation of additional scenario opportunities. Therefore, the combination of a separate youth foresight and youth entrepreneurship in the framework of other foresight projects allows you to differentiate factor analysis and use all the methods of foresight research more effectively.